ANALISIS RESIKO MUSCULOSKELETAL DISORDER’S MATERIAL HANDLER DI PT XYZ - Sidabutar, Ranto Damewilly; Zetli, Sri (Computer Science and Industrial Engineering, 2023)
Ergonomics is the art, science, and application of technology used to balance the environments in which people work or rest with their physical and psychological capabilities and limitations so that the overall quality of life can be better. High demands on Material Handlers at PT XYZ are required to complete the delivery of goods on time, where in a survey conducted by Material Handler employees spend 65% of their time completing the delivery of goods. Work like this is associated with several ergonomic risks, especially the risk of musculoskeletal disorders. For precisely determining worker posture, REBA or Rapid Entire Body Assessment is a helpful technique. The highest number of respondents a total of 23 reported experiencing waist pain in the questionnaire's results for the 8 workers. with a 71.87%. Then the next largest number feels pain in the hip with a total of 22 or 68.75%. Furthermore, they felt pain in the upper right arm as much as 21 or 65.62%. It can be concluded that Material Handler activities can cause musculoskeletal disorder injuries.